The necessity of administrating antibiotic prophylaxis to patients with diabetes mellitus prior to oral surgical procedures-a systematic review. Issue 10 (October 2022) - Sykara, Maria; Maniatakos, Panagiotis; Tentolouris, Anastasios; Karoussis, Ioannis K.; Tentolouris, Nikolaos
Abstract: Background and aims: Μany studies suggest the use of antibiotic prophylaxis (AP) as an appropriate preventive measure for patients with diabetes mellitus (DM) due to the increased possibility of an impaired wound healing and infections after surgical procedures in the oral cavity. Existing recommendations regarding antibiotic prophylaxis before surgical procedures are not definitive and are based on expert opinions. The purpose of this study was to review the available scientific data about the necessity of administrating AP as a preventive measure prior to oral surgical procedures. Method: PubMed®, Scopus® και Cochrane Central Register of Controlled Trials (CENTRAL) were used as databases to search for published research. All articles were initially identified and classified based on the title and subsequently on their abstract. For the next level the full scientific paper was read and evaluated. Results: Overall, 22 articles were included in the study, of which 2 were systematic reviews, 2 cohort studies, 2 case-control studies, 1 case series, 8 case reports and 7 professional association publications. Conclusions: In the scientific literature, there is a wide range of recommendations and inconsistency regarding the need to administer AP prior to surgical dental operations in patients with DM, while there is no scientific evidence demonstrating its' effectiveness as a precautionary measure. Both blood glucose level measurements and recent HbA1c measurement should be evaluated before any dental procedure. Poor regulation may result to life-threatening infections after tooth extraction. AP is recommended prior to the placement of dental implant. Randomized, controlled, clinical trials with large number of participants and greater variety of surgical dental procedures are needed. Highlights: Existing recommendations regarding antibiotic prophylaxis before surgical procedures are not definitive and are based on expert opinions. Both blood glucose level measurements and recent HbA1c measurement should be evaluated before any dental procedure. Poor regulation may result to life-threatening infections after tooth extraction. Antibiotic prophylaxis is recommended prior to the placement of dental implant.